2022
DOI: 10.1017/s0266467422000438
|View full text |Cite
|
Sign up to set email alerts
|

Bat diversity is driven by elevation and distance to the nearest watercourse in aterra firmeforest in the northeastern Brazilian Amazon

Abstract: Variations in environmental conditions along gradients play an important role in species distribution through environmental filtering of morphological and physiological traits; however, their effects on bat diversity remain poorly understood. Here, we investigate the effect of the distance to the nearest watercourse, terrain elevation, vegetation clutter, basal area and canopy height on taxonomic, functional and phylogenetic diversity and on the predominance of some functional traits (body mass, wing morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Ferreira et al . (2022) evaluated four bat community metrics in an Amazon Forest patch, and found that richness and diversity increased with distance to the nearest watercourse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferreira et al . (2022) evaluated four bat community metrics in an Amazon Forest patch, and found that richness and diversity increased with distance to the nearest watercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating bat communities across Mexico, Grimshaw and Higgins (2017) reported that different combinations of latitude, longitude, temperature and precipitation were most closely correlated with three measures of community diversity. Ferreira et al (2022) evaluated four bat community metrics in an Amazon Forest patch, and found that richness and diversity increased with distance to the nearest watercourse. In particular, the ecology of bat assemblages in Neotropical savanna ecosystems is poorly known.…”
Section: Discussionmentioning
confidence: 99%